Regional Innovation System in West Transdanubia - Csizmadia, Zoltán; Grosz, András (Discussion Papers, 2012)
The paper is aimed at revealing and presenting the innovation processes in West Transdanubian Region, which has one of the most successful transitions to market economy in Hungary. The paper is based on detailed enterprise surveys and expert interviews with supply side of innovation system carried out in 2006-2007. The research is aimed at presenting an overview on all the major dimensions of regional innovation system with going to analyse the following topics: a) the region’s location, information on general socio-economic trends with special regard to the prominent role of innovation policy and its network instruments; b) analysing the region’s innovation and research-development potential (based mostly on secondary data); c) mapping the innovation activities of the region’s business organisations; d) the innovation service demands of business enterprises; e) mapping the supply side of innovation services; and f) a complex evaluation on the region’s innovation system and outlining an ideal system of regional innovation. All in one this paper’s primary intention is providing a synthesis on the practical experiences, results and inter-connections based on the three year period of research and on the ten year experiences gained in innovation policy as well as presenting and highlighting how an empirical ‘screening’ of a regional innovation system may contribute to turn planning and development processes into success stories.